On the Optimization of Hydrolysis Conditions for Simultaneous Determination of Amino Acids and Amino Sugars in Marine Sediments - Priotto, Santiago (2013)
In the present work different approaches were tested for the optimization of the hydrolysis conditions for the joint determination of amino acids and amino sugars in chitin, an important structural polymer in fungi, invertebrates, algae and the exoskeleton of zooplankton. Ten treatments were evaluated, involving different combinations of hydrolysis temperature and duration. The obtained results indicate that slightly lower temperatures (105ºC) than for the classical combined amino acid hydrolysis and longer times (22 hours) than for chitin minimized losses and maximized recoveries of monomeric amino acids and amino sugars. This represents a large advantage in comparison to the usual methods of separate hydrolysis for high-performance liquid chromatography (HPLC) determination, allowing a simultaneous analysis of both compound classes in a single run.